Poly (lactic-co-glycolic acid)-encapsulated iodine-131 nanoparticles fabricated with rhTSH induce apoptosis and immobilization of thyroid cancer cells - Fan, Yongzeng; Xiong, Yalan; Wang, Xinhong; Chen, Jiahao; Fang, Danzhou; Huang, Jiahui; Yuan, Gengbiao (Frontiers in Oncology, 2023)
Aggressive thyroid carcinoma (ATC) usually loses radioiodine avidity to iodine-131 (131I) due to the downregulation of sodium/iodide symporter (NIS). The expression of thyroid stimulating hormone receptor (TSHR) is more persistent than NIS and the administration of recombinant human thyroid stimulating hormone (rhTSH) promotes de novo NIS synthesis. Hence, exploring methods integrating 131I with rhTSH might be a feasible therapeutic strategy for selective delivery of 131I into thyroid cancer to fortify the effect of radioiodine ablation. Here, our results showed that the method of developing nanoparticles-encapsulated 131I using poly (lactic-co-glycolic acid) (PLGA) and decorated with rhTSH (131I-PLGA-rhTSH), was a feasible avenue for the integration of 131I and rhTSH. Meanwhile, the encapsulation efficiency (EF) of 131I-PLGA-rhTSH nanoparticles was approximately 60%, and the radioactivity of a single nanoparticle was about 1.1×10-2 Bq. Meanwhile, the 131I-PLGA-rhTSH nanoparticles were selectively delivered into, gradually enriched and slowly downregulated in xenograft tumor after the administration of 131I-PLGA-rhTSH nanoparticles through tail vein in mouse tumor xenograft model. Thereafter, the tumor weight was significantly reduced after the administration of 131I-PLGA-rhTSH nanoparticles. Subsequently, the application of 131I-PLGA-rhTSH nanoparticles facilitated apoptosis and attenuated immobilization of FTC-133 cells. Collectively, the present study develops a suitable approach integrating 131I and rhTSH, and this strategy is a feasible regimen enhancing the effect of radioiodine ablation for the treatment of thyroid cancer.